Challenges Hindering Academic Staff in Nigerian Tertiary Education from Securing Local and International Grants: A Descriptive Study: Tantangan yang Menghambat Staf Akademik di Pendidikan Tinggi Nigeria dalam Mendapatkan Hibah Lokal dan Internasional: Sebuah Studi Deskriptif - Ogunode, Niyi Jacob; D. M , Gregory (Indonesian Journal of Innovation Studies, 2023)
This descriptive research aims to evaluate the perceptions of academic staff regarding the factors impeding their success in obtaining both local and international grants within Nigerian tertiary education. Employing a sample size of 240 participants from six federal universities spanning diverse geopolitical zones, a multistage sampling technique was applied. A bespoke questionnaire, "Perception of Academic on Reasons Why Academic Staff of Nigerian Tertiary Education are not Wining Local and International Grants (PASRWNWLGQ)," was utilized for data collection. The instrument demonstrated high reliability with a coefficient of 0.86. Analysis involved descriptive statistics, yielding insights into various barriers including inadequate research proposal planning, limited awareness of grant opportunities, and challenges associated with online application procedures. The study highlights the urgent need for enhanced research funding in Nigerian tertiary institutions to address these impediments. Furthermore, findings illuminate the broader consequences, encompassing diminished research development, brain-drain, and weakened international rankings, alongside dwindling morale among academic staff. This study provides critical insights for policy makers and stakeholders seeking to bolster the research landscape in Nigerian tertiary education. Highlight: The study encompasses 240 participants from six federal universities in Nigeria, offering a comprehensive perspective on the challenges faced by academic staff in securing both local and international grants. The research instrument, "Perception of Academic on Reasons Why Academic Staff of Nigerian Tertiary Education are not Wining Local and International Grants (PASRWNWLGQ)," demonstrates a high level of reliability (coefficient of 0.86), ensuring robust data collection and analysis. The findings shed light on critical barriers, such as deficient research proposal planning, limited awareness of grant opportunities, and online application challenges, underscoring the pressing need for increased research funding in Nigerian tertiary institutions. The study also unveils far-reaching repercussions, including stunted research development, brain-drain, and a decline in international rankings, emphasizing the urgency of policy interventions to fortify the research landscape. Keyword: Perception, Academic Staff, Grants, Nigerian Tertiary Education, Research Funding